Allopregnanolone and puberty: modulatory effect on glutamate and GABA release and expression of 3-hydroxysteroid oxidoreductase in the hypothalamus of female rats. - Giuliani, Fernando Alfredo (2013)
The hypothalamic release of glutamate and GABA regulates neurosecretory functions that may control the onset of puberty. This release may be influenced by neurosteroids such as allopregnanolone. Using superfusion experiments we examined the role of allopregnanolone on the K+-evoked and basal [3H]-glutamate and [3H]-GABA release from mediobasal hypothalamus and anterior preoptic area in prepubertal, vaginal opening and pubertal (P) rats and evaluated its modulatory effect on GABAA and NMDA (N-methyl-d-aspartic acid) receptors. Also, we examined the hypothalamic activity and mRNA expression of 3α-hydroxysteroid oxidoreductase (3α-HSOR) ? enzyme that synthesizes allopregnanolone ? using a spectrophotometric method and RT-PCR, respectively. Allopregnanolone increased both the K+-evoked [3H]-glutamate and [3H]-GABA release in P rats, being the former effect mediated by the modulation of NMDA receptors ? as was reverted by Mg2+ and by the NMDA receptor antagonist AP-7 and the latter by the modulation of NMDA and GABAA receptors ? as was reverted by Mg2+ and the GABAA receptor antagonist bicuculline. The neurosteroid also increased the basal release of [3H]-glutamate in VO rats in an effect that was dependent on the modulation of NMDA receptors as was reverted by Mg2+. On the other hand we show that allopregnanolone reduced the basal release of [3H]-GABA in P rats although we cannot elucidate the precise mechanism by which the neurosteroid exerted this latter effect. The enzymatic activity and the mRNA expression of 3α-HSOR were both increased in P rats regarding the other two studied stages of sexual development. These results suggest an important physiological function of allopregnanolone in the hypothalamus of the P rat where it might be involved in the ?fine tuning? of neurosecretory functions related to the biology of reproduction of the female rats.